Computers as Social Actors? Examining How Users Perceive and Interact with Virtual Influencers on Social Media - Park, Gyeongbin; Nan, Dongyan; Park, Eunil; Kim, Ki Joon; Han, Jinyoung; del Pobil, Angel P. (2021 15th International Conference on Ubiquitous Information Management and Communication (IMCOM), 2021)
With the rapid development of s-commerce and CGI technology, the concept of "virtual influencer" has emerged and is rapidly growing in popularity in social media and network service (e.g., Instagram). This paper investigated the effects of the number and types of social actors in the contents of Instagram on users' reactions. To identify this, we collected the users' comments from the contents of the virtual influencers' accounts on Instagram and conducted sentiment analysis. The results showed that users tend to use more social words and 3rd-person pronouns in contents with multiple social actors including the virtual influencer than in contents with a virtual influencer. Moreover, when a virtual influencer is presented in the contents of social media with humans, users tend to use more positive words and anxious words than in the contents without humans. Based on these outcomes, several interesting issues are discussed below.